Gut Microbiome and Bile Acid Metabolism Induced the Activation of CXCR5+ CD4+ T Follicular Helper Cells to Participate in Neuromyelitis Optica Spectrum Disorder Recurrence - Cheng, Xi; Zhou, Luyao; Li, Zhibin; Shen, Shishi; Zhao, Yipeng; Liu, Chunxin; Zhong, Xiaonan; Chang, Yanyu; Kermode, Allan G.; Qiu, Wei (Frontiers in Immunology, 2022)
From the perspective of the role of T follicular helper (Tfh) cells in the destruction of tolerance in disease progression, more attention has been paid to their role in autoimmunity. To address the role of Tfh cells in neuromyelitis optica spectrum disorder (NMOSD) recurrence, serum C-X-C motif ligand 13 (CXCL13) levels reflect the effects of the Tfh cells on B-cell-mediated humoral immunity. We evaluated the immunobiology of the CXCR5+CD4+ Tfh cells in 46 patients with NMOSD, including 37 patients with NMOSD with an annual recurrence rate (ARR) of<1 and 9 patients with NMOSD with an ARR of ≥1. Herein, we reported several key observations. First, there was a lower frequency of circulating Tfh cells in patients with an ARR of<1 than in those with an ARR of ≥1 (P< 0.05). Second, the serum CXCL13 levels were downregulated in individuals with an ARR<1 (P< 0.05), processing the ability to promote Tfh maturation and chemotaxis. Third, the level of the primary bile acid, glycoursodeoxycholic acid (GUDCA), was higher in patients with NMOSD with an ARR of<1 than in those with NMOSD with an ARR of ≥1, which was positively correlated with CXCL13. Lastly, the frequency of the Tfh precursor cells decreased in the spleen of keyhole limpet haemocyanin-stimulated animals following GUDCA intervention. These findings significantly broaden our understanding of Tfh cells and CXCL13 in NMOSD. Our data also reveal the potential mechanism of intestinal microbiota and metabolites involved in NMOSD recurrence.